Pop!. by roderick hunt, kate ruttle - Hunt, Roderick ([S.l.] : Oxford University Press, 2011)
Engaging decodable stories fully aligned to Letters and Sounds enable your pupils to practise their phonics skills with their favourite characters. Written by Roderick Hunt and illustrated by Alex Brychta, award-winning creators of the Oxford Reading Tree. Six engaging stories at Level 1+ provide focused practice of phonics at Letters and Sounds Phase 2. Books contain inside cover notes to support children in their reading. Help with childrens reading development is also available at www.oxfordowl.co.uk. There are 6 Floppy's Phonics Fiction titles available at Level 1+: Cats: Kipper is the top cat. Big, Bad Bug: Dad has a big bug! Pop!: Kipper tips the popcorn in. Mud!: There is mud on the dog! Hats: Mum has a mad hat! A Big Mess: There is a big mess on the mat.